Effect of the Proximity of Roots to the Cortical Plate and Inclination of Incisors on External Apical Root Resorption - Shivam Mehta; Po-Jung Chen; Meng-Hsuan Lin; Gauri Sharma; Falguni Mehta; Chia-Ling Kuo; Aditya Tadinada; Sumit Yadav (Wolters Kluwer Medknow Publications, 2024)
Background: External apical root resorption (EARR) is an unfavorable side effect of orthodontic treatment. Orthodontic treatment of patients with increased crowding could lead to the proclination of incisors and proximity of roots to the cortical plates. Aims: The aim of this study was to evaluate the effects of the proximity of the labial and lingual cortical plates and the inclination of incisors on EARR. Settings and Design: Twenty-six patients (age: 13.39 years) with nonextraction fixed orthodontic treatment were evaluated at pretreatment and posttreatment (52 cone-beam computed tomographies). Materials and Methods: The maxillary and mandibular incisors (416 teeth) were evaluated for the pretreatment predictors such as the labial and palatal (lingual) cortical plate thickness, width of the mandibular symphysis/maxillary alveolus and cancellous bone, position of the root apex in cancellous/cortical bone, and treatment factors such as distance of root to the labial and palatal (lingual) outer and inner cortical plate and incisor inclination. Statistical Analysis Used: Statistical analyses were performed with R software at a 0.05 significance level. Each parameter was compared between pretreatment and posttreatment by a paired t-test, and the association to root resorption was performed using a regression model. Results: Clinically significant (>1 mm) root resorption was observed in 35% of all mandibular incisors and 52% of all maxillary incisors. Width of cancellous bone, position of the root apex in cortical bone, proximity of the root apex to the labial and palatal (lingual) outer cortical plate, lingual inner cortical plate, and proclination of incisors were significant factors associated with EARR. Conclusions: Proximity to the cortical plates and proclination of incisors are associated with increased EARR.